Integrasi Matematika, Nilai-Nilai Keislaman, dan Teknologi: Fenomena di Madrasah Tsanawiyah - Wilda Yumna Safitri; Haryanto Haryanto; Imam Rofiki (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
A study of mathematics integration with technology and Islamic values becomes an interesting topic to be studied by many scholars. The mathematics integration is essential to be applied in learning so that it can make students become Muslim individuals who have excellent character and proficiency in utilizing technology. However, there are still few studies that investigate mathematics integration with technology and Islamic values. Therefore, this study aims to describe phenomena directly related to mathematics learning that contain Islamic values and the use of technology in the learning process. The type of this study was descriptive research using a qualitative approach. The subjects of this study were three mathematics teachers who teach at Madrasah Tsanawiyah (MTs). The study procedure was carried out to find the phenomenon of research subjects that occurred at MTs. The validity of the data used the triangulation of the source and method. Data were collected through literature review, interview, and observation. The study results showed that three MTs had applied Islamic values and technology content in mathematics learning. This study recommends the need for innovation in MTs to design mathematics-integrated learning with Islamic values and the use of technology to help teachers create efficient learning, attract students' learning interest, and create an active learning environment for students.